Scapular shape of extant hominoids and the African ape/modern human last common ancestor. Issue 94 (May 2016) - Green, David J.; Spiewak, Ted A.; Seitelman, Brielle; Gunz, Philipp
Abstract: Newly discovered early hominin fossil scapulae have bolstered investigations of scapular shape, which have long been used to interpret behavioral variation among primates. However, unexpected similarities between Pongo and Homo – particularly in scapular spine orientation – have raised questions about the functional utility of scapular morphology and its phylogenetic context in the hominin lineage. Not surprisingly, significant disagreement surrounds disparate morphological reconstructions of the modern human/African ape last common ancestor (LCA). Our study utilizes geometric morphometric (GM) approaches – two employing homologous, anatomical landmarks and a "spine-free" alternative using 98 sliding semilandmarks along the boundary of the subscapular fossa. The landmark-based "wireframe" GM analysis principally sorted groups by spine orientation: Homo and Pongo were similar to one another with more transversely-oriented spines as compared to Hylobates and the African apes. In contrast, Homo and Gorilla clustered together in our semilandmark analysis with superoinferiorly broad blades. Pan scapulae were similar, but had more mediolaterally compressed blades and laterally-positioned superior angles. Hylobates was superoinferiorly narrow, yet obliquely expanded relative to the vertebral border. Pongo scapulae were unique among hominoids in being nearly as broad as they were long. Previously documented 'convergence' of Homo and Pongo scapulae appears to be principally driven by similarities in spine orientation, rather than overall blade shape. Therefore, we contend that it is more parsimonious to reconstruct the African ape/ Homo LCA scapula as being Gorilla -like, especially in light of similar characterizations of certain fossil hominin scapulae. Accordingly, the evolution of Pan (highly oblique spine and laterally-situated superior angle) and Homo (transversely-oriented spine) scapular morphology would have involved relatively minor shifts from this ancestral condition. These results support the prevailing molecular phylogeny and provide further insight into the behavioral implications of scapular shape in the LCA and fossil hominins.